Penggunaan Identitas Relijius dalam Naratif "Qorin" (2022): Sebuah Studi "New Historicism". - Santabudi, Bisma; Paulus Heru Wibowo Kurniawan; Frans Sahala Moses (Widya Winayata : Jurnal Pendidikan Sejarah, 2024)
Qorin (2022) is one of the contemporary Indonesian horror films that incorporates Islamic religious elements as a theme in its narrative. This research aims to examine the use of religious identity both audio and visual in the narratives of contemporary horror films in Indonesia. The research method used is qualitative description with content analysis. The theory used to examine the film is the theory of New Historicism. Through this theory, the film Qorin (2022) will be examined based on 2 things: the interdiscursivity of the film text with texts outside the film and the world or meaning to be depicted in the film. The conclusion of this research shows that the movie Qorin provides an overview of the socio-cultural conditions that occur in Indonesia through religious identity. This can be seen especially in the relationship between religious leaders and their followers.